2018
DOI: 10.1002/jbmr.3587
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Weight Gain and Offspring Bone Mass: Different Associations in Healthy Weight Versus Overweight Women

Abstract: Weight management strategies during pregnancy reduce child cardiometabolic risk. However, since maternal weight has an overall positive correlation with offspring bone mass, pregnancy weight management could adversely affect child bone health. We aimed to estimate associations between gestational weight gain (GWG) and bone mineralization in the offspring at 7 years of age, and test early pregnancy body mass index (BMI) as an effect modifier. We analyzed prospective data from 2,167 mother-child pairs from the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The differences between maternal 25(OH)D categories and GWG categories in whole-body BMC (g) and BMC per body weight (BMC/kg; g/kg), lumbar spine BMC (g), and BMD (g/cm 2 ) were tested using a mixed linear model. The variables tested as fixed effects were considered based on previous research, including infant sex [40,41], age [42], and length-for-age z-scores (LAZ) [43]; maternal characteristics: 25(OH)D categories [11,24], pre-pregnancy BMI categories [14], GWG categories [38], gravida [44], and age [45]; and sociodemographic characteristics [46][47][48]: maternal education and self-reported population group, and annual family income. Given that GWG may be an effect modifier of the maternal vitamin D status-infant bone outcomes association [19], both factors were tested in the same model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The differences between maternal 25(OH)D categories and GWG categories in whole-body BMC (g) and BMC per body weight (BMC/kg; g/kg), lumbar spine BMC (g), and BMD (g/cm 2 ) were tested using a mixed linear model. The variables tested as fixed effects were considered based on previous research, including infant sex [40,41], age [42], and length-for-age z-scores (LAZ) [43]; maternal characteristics: 25(OH)D categories [11,24], pre-pregnancy BMI categories [14], GWG categories [38], gravida [44], and age [45]; and sociodemographic characteristics [46][47][48]: maternal education and self-reported population group, and annual family income. Given that GWG may be an effect modifier of the maternal vitamin D status-infant bone outcomes association [19], both factors were tested in the same model.…”
Section: Discussionmentioning
confidence: 99%
“…This is exemplified in the Avon Longitudinal Study of Parents and Children in which maternal exposure to ultraviolet B (UVB) radiation and folate intake during pregnancy were both positively related to childhood (9 years of age) bone mineral content (BMC) and bone mineral density (BMD) [4]. Other maternal factors related to an offspring's bone outcomes include maternal smoking [5] and alcohol consumption [6] that are negatively related to bone outcomes, whereas the relation of maternal vitamin D supplementation [7][8][9], vitamin D status [10][11][12][13], pre-pregnancy body mass index (BMI), and gestational weight gain (GWG) [14] to infant bone outcomes is equivocal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, no association was found [ 31 ], whereas in another study a positive association was noticed but only in relation to one of the measured sites (LS BMD) [ 53 ]. The influence of pregnancy weight gain, which was investigated in three studies [ 53 , 55 , 56 ], was also ambiguous. In a study by Xu et al [ 56 ], pregnancy weight gain was positively related to offspring BMD.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In another study, a positive influence was observed only in relation to one measured site (TB BMD) [ 53 ]. Monjardino et al [ 55 ] found that maternal gestational weight gain (GWG) was associated with higher aBMD in children, but only if the mothers were under/normal weight at the beginning of pregnancy.…”
Section: Findings and Discussionmentioning
confidence: 99%